What do we know about our agency nurse population? A scoping review. Issue 4 (10th July 2019) - Simpson, Kate; Simpson, Richard
Abstract: Background: Nurse staffing shortages are often managed by using temporary staff. This review discovers what is known about nurses who choose to work in this way. Procedure: A literature search found eight international studies investigating the lived experience of agency nurses. Results: Nurses actively choose agency nursing to work flexibly and avoid office politics or as a career stop‐gap. However, respondents describe feeling isolated, working difficulties with permanent staff and fewer opportunities for training. Conclusions: Though participants described positive reasons for choosing agency nursing, there were significant downsides. The findings must be viewed in the context of the continued feminized nature of the nursing profession as care responsibilities were cited as a reason for choosing this study pattern. However, the lack of security and provision of adequate pensions and career advancement are considerable issues. The costs of using agency staff are high and consideration must be given to encouraging these nurses into substantive contracts. These individuals show considerable resilience, flexibility, and varied expertise. Such qualities are vital for health care in the 21st century and understanding why they opt out of permanent nursing will enable employers to adapt practices to harness this. Suggestions for practice and further research are presented.